Liquid-gated Field-effect-transistor Based on Chemically Reduced Graphene Oxide for Sensing Neurotransmitter Acetylthiocholine - Nguyen, Thi Thanh Ngan; Vu, Thi Thu; Nguyen, Danh Thanh; Nguyen, Thi Lan; Duong, Thanh Tung; Cao, Thi Thanh; Nguyen, Van Chuc (Communications in Physics, 2022)
In this work, an enzymatic liquid-gated field-effect-transistor sensor based on chemically reduced graphene oxide film was develop for determination of acetylthiocholine in aqueous conditions. The device was designed with interdigitated electrode configuration and then manufactured by combining lithography and chemical vapor deposition techniques in clean room. Graphene oxide material (prepared by Hummer method) was chemically reduced using a strong reducing agent hydrazine, and then drop-casted onto the channel region. The results have demonstrated a successful reduction of graphene oxide with clearly shifting of 02 characteristic peaks comparing with graphene oxide. Consequently, the transfer curve of as-prepared reduced graphene oxide based transistor exhibits ambipolar characteristics with a V-shape. Acetylcholinesterase was immobilized on top of reduced graphene oxide film with the aid of glutaraldehyde trapping agent. It was found that the release of proton from enzymatic hydrolysis of acetylthiocholine has caused significant variation in charge concentration and mobility in the channel, thus generated a significant blue shift in position of Dirac point on ambipolar curve. The developed sensor exhibits good sensing performances with LOD of 250 µM in concentration range 0 – 0.8 mM.